Bagaimana Loyalitas Pengguna Insurtech Terbentuk Melalui Pengalaman Pelanggan - Vania Rachma Putri; Arviansyah Arviansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Digital Application Insurance is emerging as a significant corporate customer-facing application, potentially increasing customer service efficiency while reducing costs. However, little work has attempted to assess the quality of the services they provide to consumers. This study applies e-service service quality & e-recovery service quality with digital applications to predict user experience, satisfaction and loyalty towards digital applications. This research was planned to use a quantitative approach, with data obtained from two primary sources, where the sample for this research proposal was a minimum of two hundred respondents using a questionnaire. The structural equation modeling method was carried out to test the research hypothesis. The hypothesis will show that the e-quality service and recovery service factors have a positive effect on customer loyalty. It is hoped that this study can contribute to digital applications in developing their services by examining the impact of efficiency, provision, security, availability and synchronization, responsiveness, contact. This research highlights new concepts regarding digital e-service and e-recovery service applications. Previous research used customer service chatbots components that measured efficiency, fulfillment, security, availability and compensation, responsiveness, contact. So, this research is to provide valuable insights to insurance management and marketers to develop better services. Keywords: Electronic service quality, E-recovery service quality, customer satisfaction, customer experience, customer loyalty.